Cold Enrichment Methods for the Detection of Foodborne Yersiniosis: Friend or Foe? - Yuwei Zhang; Stephen L. W. On (Pathogens, 2022)
Yersinia enterocolitica and Y. pseudotuberculosis are important causes of enteric illness worldwide. Rapid response to suspected foodborne outbreaks is hampered by the widespread use of cold enrichment methods that require incubation periods of 10–21 days. Although these species grow faster at elevated temperatures, part of the rationale for cold enrichment is that a key pathogenicity marker (pYV virulence plasmid) is said to be lost at elevated temperatures. Experimental data on this claim seems scarce. We previously described an approach involving an enrichment step at 37 °C for Yersinia detection, applied this approach to additional strains, and examined the presence of plasmids in reisolates, as well as those recovered in our original study. Plasmids were recovered from every reisolate examined; the presence of marker genes yadA and virF denoted the virulence plasmid in 10 of the 11 strains examined. Use of an enrichment step at 37 °C does not appear to promote loss of the pYV or other plasmids harboured by foodborne pathogenic Y. enterocolitica and Y. pseudotuberculosis; wider adoption of this approach may assist the development of more rapid detection methods.